Student’s perception of residential hall safety and security in UUM Campus - Lim, Ooi Yee; Noordin, Alminnourliza (Universiti Utara Malaysia, 2020)
This aims of this study is to study the perceptions of Universiti Utara Malaysia (UUM) students toward residential hall safety and security and proposing ways to improve residential hall safety in UUM. Safety and security of residential halls are very important because a safe environment has long been considered a prerequisite for effective learning. However, it is not safe even in university. Problems like theft, burglary, bully, sexual harassment and other problems have occurred in other schools. Thus, this study focuses on identifying the perception of UUM students whether they feel safe or not, if not, how to improve the safety of the residential hall in UUM? This study design used a qualitative research method. The respondents are the students of each residential hall in UUM. The result showed that a majority of the students feel safe in the residential hall and a minority of them unsatisfied about the safety in the residential hall. Regardless of satisfaction or dissatisfaction, they provided a lot of suggestions to improve the safety of the residential hall. This study raises awareness for students to pay attention to their safety and improve the safety of the UUM residential hall.